Education and Screening for Stunting Risk in Women of Reproductive Age and Pregnant Women in Muara Jawa Ulu Village (JURNAL PENGMAS KESTRA (JPK), 2025)
Stunting is a public health problem that remains a challenge in Indonesia because it impact long-term child growth and development. Preventive efforts should be implemented starting from the preconception and pregnancy stages through improve knowledge and early detection of risk factors among pregnant women and women of reproductive age. This community service activity aimed to increase the knowledge of pregnant women and women of reproductive age regarding stunting prevention through educational interventions and basic nutritional status assessments. The activity was conducted in Muara Jawa Ulu Village Kutai Kartanegara Regency East Kalimantan Province, over a four month period in 2025, involving 47 participants consisting of pregnant women and women of reproductive age. The implementation methods included health education through interactive lectures, group discussions, and question and answer sessions, as well as early detection examinations such as hemoglobin (Hb) measurement, mid-upper arm circumference (MUAC), and proteinuria testing. Knowledge evaluation was conducted through pre and post tests using questionnaires analyzed by Paired Sample T-Test. The results showed that 10.6% of participants experienced Chronic Energy Deficiency (MUAC < 23.5 cm) and 40.4% had anemia, while all participants tested negative for proteinuria. There was a significant improvement in participants knowledge after the educational intervention, with the mean pre-test score increasing from 15.00 to 17.23 (p = 0.0001). This activity proved effective in improving participants knowledge and awareness of stunting prevention and in strengthening collaboration between universities, health workers, and integrated health post (Posyandu) cadres in community-based health promotion efforts. It is expected that this initiative can serve as a sustainable model for stunting prevention programs within the community.